Applications of Learning Analytics in High Schools: A Systematic Literature Review - Sousa, Erverson B. G. de; Alexandre, Bruno; Ferreira Mello, Rafael; Pontual Falcão, Taciana; Vesin, Boban; Gašević, Dragan (Frontiers in Artificial Intelligence, 2021)
Learning analytics aims to analyze data from students and learning environments to support learning at different levels. Although learning analytics is a recent field, it reached a high level of maturity, especially in the applications for higher education. However, less research in learning analytics targets other educational levels, such as high school. This paper reports the results of a systematic literature review (SLR) focused on the adoption of learning analytics in high schools. More specifically, the SLR followed four steps: the search, selection of relevant studies, critical assessment, and the extraction of the relevant field, which included the main goals, approaches, techniques and challenges of adopting learning analytics in high school. The results show that, in this context, learning analytics applications are focused on small-scale initiatives rather than institutional adoption. Based on the findings of this study, in combination with the literature, this paper proposes future directions of research and development in order to scale up learning analytics applications in high schools.